Long‐term respiratory outcomes after primary total correction for tetralogy of Fallot and absent pulmonary valve in patient with respiratory symptoms. (19th May 2017) - Hoashi, Takaya; Iwasa, Toru; Kagisaki, Koji; Shimada, Masatoshi; Kurosaki, Kenichi; Shiraishi, Isao; Ichikawa, Hajime
Abstract: Objective: To review long‐term respiratory outcomes for tetralogy of Fallot and absent pulmonary valve (TOF/APV) in respiratory symptomatic populations. Methods: Of 25 consecutive patients undergoing primary total correction for TOF/APV between 1987 and 2016, Sixteen patients (64%) with a preoperative respiratory disturbance were enrolled. The median age at operation was 1.9 months old, including 4 neonates and 12 infants. Ten patients (62.5%) preoperatively necessitated mechanical ventilator support. During operation, dilated central pulmonary arteries (cPAs) were plicated and retracted anteriorly in all patients, except for the first patient of the study cohort. VSD was completely closed, and the right ventricular outflow tract was reconstructed with a handmade valved conduit before 1990, or a transannular patch with a handmade monocusp after 1991. Results: The actuarial survival rate at 20 years was 86.7%. One patient without cPAs plication and another requiring mechanical ventilator support right after his delivery died. The median duration of postoperative mechanical ventilator support was 14 days (range, 1–183). Readmission for respiratory disturbance after discharge was frequently observed before five years of age, however, no patients were readmitted to the hospital after six years of age, during the median follow‐up period of 14.7 years, with a maximum of 27.2 years. Although persistent dilatation of cPAs was common, respiratory symptoms never recurred. Conclusions: Prognostic and respiratory outcomes after primary total correction for TOF/APV in respiratory symptomatic populations were good. Successful relief of tracheal/main bronchial compression by primary total correction at the neonatal or infantile period provided delayed, but nonrecurrent improvement of respiratory disturbances.